Root System Traits and Their Association with The Yield of Safflower under Different Irrigation Regimes - Ganji, Masomeh; Galeshi, Serolah; Jabbari, Hamid; Sanjarian, Forough; Torabi, Benjamin (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2025)
Root system is recognized to play a crucial role in enhancing plant tolerance and stability during drought conditions. Therefore, this study aimed to assess safflower (Carthamus tinctorius L.) genotypes under various irrigation regimes and explore the relationship between root traits and yield. A two-year factorial experiment was conducted with three spring safflower genotypes, namely Parnian, Goldasht, and Kazak under two irrigation regimes, including full and deficit. Irrigation treatments maintained residual moisture levels at 60% and 20% of available water. Root traits such as biomass (RB), length (RL), diameter (RD), dry weight (RDW), and root length density (RLD) were measured. Additionally, seed yield (SY), yield components, and oil content (OC) were assessed in all treatments. The results showed that drought stress reduced safflower RB and RL, but Kazak genotype had a significant increase in RDW (48%) and RL (12%) under deficit irrigation. Root biomass distribution and RLD varied among genotypes across soil layers. Parnian and Goldasht genotypes had the highest root biomass at 30 cm depth with full irrigation, while Kazak showed the highest values at 60-90 cm depth under deficit irrigation. Drought stress significantly reduced safflower SY by 71% and Kazak genotype showed the highest SY under deficit irrigation, suggesting better performance stability. SY had a strong positive correlation with RDW (0.57) and RD (0.84), indicating a significant relationship. Furthermore, SY was significantly correlated with RLD at depths of 60-90cm (0.72-0.68). These results suggested that root traits such as RDW, RD, and RLD in deeper soil layers were crucial for breeding programs aiming to develop drought-tolerant genotypes.